Experimental study on the residual interfacial bonding performance between CFRPs and concrete after high temperatures - Yushi Yin; Qinhua Yang; Zhihui Zhang; Haiyang Luan; Chen Li (Advances in Bridge Engineering)
Abstract Carbon fibre reinforced polymer (CFRP) are widely used in bridge reinforcement projects. However, delamination at the CFRP-concrete interface caused by frequent fires significantly impacts structural safety, severely restricting the further and extensive development of CFRP in bridge engineering. In this paper, the sand filling method is used to quantitatively evaluate the roughness of the concrete beam's surface, and the interfacial normal and tangential bonding stresses between CFRPs and concrete after exposure to elevated temperatures were investigated. The strength grade of the concrete, concrete surface roughness and temperature were analysed to explore the behaviour of the CFRP composites. First, before the CFRP sheets were pasted, the concrete interfacial roughness was quantitatively evaluated, and 135 CFRP-concrete interfacial bonding tests were carried out. Then, two bonding models based on an elevated temperature field were proposed. Finally, the interfacial bonding failure mechanism was analysed by scanning electron microscope (SEM). The research results showed that the concrete surface roughness more significantly affects the interfacial bonding stress than does the strength grade of the concrete. The interfacial separation between CFRPs and epoxy resin occurs at 110 °C, and the glass transition temperature (Tg) is the critical factor determining the decrease in the bonding performance of CFRP composites. The two models proposed in this study exhibit high prediction accuracy and certain safety reserves and are applicable to the prediction of CFRP reinforcement design and construction after exposure to high temperatures. These models also have additional potential applications.